Percival the plain little caterpillar - Brawley, Helen (Sydney : The Book Company Publishing, 2001)
"Percival slept for a very long time. He dreamed of green and red and blue and pink and purple and yellow. And when he woke up, something wonderful had happened!"--Cover.
On board pages.
Contains holographic paper inserts.
Keywords: Children's stories